Alcohol-related protective behavioral strategies as a mediator of the relationship between drinking motives and risky sexual behaviors. (June 2019) - Looby, Alison; Bravo, Adrian J.; Kilwein, Tess M.; Zimmerman, Lauren; Pearson, Matthew R.; ,
Abstract: Risky sexual behaviors (RSB) frequently occur in the context of alcohol use and are associated with distinct drinking motives among college students. Use of alcohol protective behavioral strategies (PBS) is associated with reductions in alcohol use and related problems, which may extend to alcohol-related RSB. Moreover, as PBS use mediates the relationship between positive reinforcement drinking motives and alcohol-related problems, the same may be true for alcohol-related RSB, specifically. The current study examined whether PBS mediates the relationship between drinking motives and RSB among college students. Participants ( N   =  2039, 72.8% female, M age  = 19.79) from ten universities across ten U.S. states completed an online survey assessing past-month drinking motivation, alcohol PBS, alcohol consumption, and RSB. To test study aims, a saturated path model in which drinking motives were modeled as predictors of RSB via PBS use subscales and alcohol consumption was conducted. Several double mediation effects were found, such that stronger endorsement of motives (i.e., social, enhancement, conformity, coping for depression) were associated with lower PBS (particularly manner of drinking and serious harm reduction), which was associated with higher alcohol use, which was associated with higher RSB. Multi-group models found the mediation effects to be gender invariant, although several differences in direct associations were found across genders. For college students high in positive reinforcement motives (i.e., social or enhancement) for drinking, interventions that aim to increase PBS use, specifically related to modifying the manner in which one drinks and avoiding very dangerous consequences, may be effective in reducing alcohol-related RSB. Highlights: Social and enhancement drinking motives are associated with risky sexual behavior. Protective behavioral strategies mediate the motives-risky sex relationship. Manner of drinking PBS mediates the relationship for both types of motives. Serious harm reduction PBS mediates the relationship only for enhancement motives.